Using AI-generative tools in tertiary education: Reflections on their effectiveness in improving tertiary students’ English writing abilities - Cheng, Ching Ho (Online Learning, 2024)
Artificial intelligence (AI) tools have become a popular topic in the education field. Most of the schools in Hong Kong focus on how to properly use AI software to help students’ learning experience. As this is still a relatively new device, the stance for most of the schools in Hong Kong is skeptical. This study aims to find out whether AL-Generative tools, such as Chatgpt, can help to improve students’ English writing skills in university. Interviews were used to find out students and teachers’ opinions towards using AI in writing. The results indicate that students find AI tools convenient for learning writing skills, but teachers are concerned that the feedback and examples provided by AI are too general and ambiguous. This study provides some interesting opinions from students and teachers about their experience in using AI in learning and writing, and this helps us to understand more about how to use AI effectively in the education sector.